Challenges experienced by immigrant entrepreneurs in a developing non-Western country: Malaysia - Hamizah Abd Hamid (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to explore the challenges experienced by immigrant entrepreneurs in a developing non-Western immigrant-receiving country. Research Design & Methods: Through a qualitative approach, this study examined the experiences of immigrant entrepreneurs from Indonesia, Pakistan, and South Korea in one host country, Malaysia. Findings: The findings suggest that the formal aspects of host country institutions are mainly instrumental in the commencement stages of immigrant entrepreneurs' ventures and the informal aspects of institutions are predominantly influential in the developmental stages of immigrant entrepreneurs' ventures. Specifically, the findings indicate that the challenges experienced by immigrant entrepreneurs in the host country mainly stem from (1) governing institutions, (2) resource-providing institutions, (3) local society and (4) competition in the host country. Implications & Recommendations: Through the model, this study provides a layer of knowledge in immigrant entrepreneurship activities conducted in developing non-Western countries, which is a fertile area of interest in immigrant entrepreneurship. Practice-wise, this study provides useful evidence in assisting immigrant entrepreneurs and host country's policymakers who deal with trade and migration to create a more sustainable landscape for immigrants to conduct entrepreneurship activities. Contribution & Value Added: This research contributes to the immigrant entrepreneurship literature by further gauging the way home-host country dynamics influence the experiences of immigrant entrepreneurs in conducting their ventures in a foreign country.
Keywords: J15; F22; L26; 330; Immigrant entrepreneurs; Malaysia; entrepreneurship